MENINJAU IMPLEMENTASI KEBIJAKAN PUBLIC SERVICE OBLIGATION DI SEKTOR TRANSPORTASI - Rastri Paramita (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2023)
This study aims to educate the public about the basis of PSO implementation, the form of PSO implementation, and the differences in PSO implementation by BUMN in the transportation sector, with examples of PSO implementation at PT Pelni and PT KAI. It is intended that by comprehending the variations in PSO implementation by BUMN, it will be possible to offer suggestions for future PSO implementation improvements. The results of studies on PSO at PT KAI and PT Pelni from journals, research, and the media were used in this study, which employed a qualitative methodology and secondary data in the form of statutory data, development data, and PSO implementation. As a result, there are discrepancies in the technological execution of the PSO for the supply of transportation services in Indonesia. This distinction sets the PSO's role not just as a government instrument to give the population, especially the poor, affordable transportation, but also as another goal to present.